2019
DOI: 10.32800/abc.2019.42.0113
|View full text |Cite
|
Sign up to set email alerts
|

Haplotypic characterization of the olive ridley turtle (Lepidochelys olivacea) in northwest Mexico: the northernmost limit of its distribution

Abstract: Haplotypic characterization of the olive ridley turtle (Lepidochelys olivacea) in northwest Mexico: the northernmost limit of its distribution. The olive ridley sea turtle (L. olivacea) has a pantropical distribution. In the Eastern Pacific, the official limits of its reproduction area are south of the Baja California peninsula and south of Sinaloa, Mexico. Ceuta beach in Elota, Sinaloa, Mexico, has served as a protection site for L. olivacea for over three decades. In this study, the L. olivacea population fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
2
8
2
Order By: Relevance
“…We observed ten ~ 800 bp haplotypes from 60 turtles nesting at Playa Nancite ( n = 7), Playa Grande ( n = 17), and Playa Ostional ( n = 36; Table 2; Figure 2 and Figure ). Overall haplotype diversity ( H = 0.5657 ± 0.0783 SD ) and nucleotide diversity (π = 0.0014 ± 0.0012 SD ) were comparable to those reported in other studies of Pacific olive ridleys (i.e., Campista León et al, 2019; Jensen et al, 2013; López‐Castro & Rocha‐Olivares, 2005) and did not vary between sites (as suggested by overlapping standard deviations; Table 2).…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…We observed ten ~ 800 bp haplotypes from 60 turtles nesting at Playa Nancite ( n = 7), Playa Grande ( n = 17), and Playa Ostional ( n = 36; Table 2; Figure 2 and Figure ). Overall haplotype diversity ( H = 0.5657 ± 0.0783 SD ) and nucleotide diversity (π = 0.0014 ± 0.0012 SD ) were comparable to those reported in other studies of Pacific olive ridleys (i.e., Campista León et al, 2019; Jensen et al, 2013; López‐Castro & Rocha‐Olivares, 2005) and did not vary between sites (as suggested by overlapping standard deviations; Table 2).…”
Section: Resultssupporting
confidence: 84%
“…There was no evidence that any of the three sites were genetically distinct from each other as determined by pairwise Φ ST ( Φ ST = −0.05–0.00021, p = .37–0.79), pairwise θ ST ( θ ST = −0.03–0.02, p = .61–0.79), and AMOVA (variance explained = −0.21%, F ST =−0.02, p = .65). We compared our data to those published for Mexican olive ridleys (Playa de Ceuta, Sinaloa; Campista León et al, 2019). Pairwise Φ st ( Φ ST = −0.017–0.00571, p = .32–.81), pairwise θ ST ( θ ST = −0.02–0.0043, p = .41–0.78), and AMOVA (variance explained = −0.13%, F ST = 0.001, p = .57) did not suggest divergence between any sampling sites.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…comm.). Genetic analysis of organisms inhabiting SPC indicated that this rockery has moderate genetic diversity that is very similar (h= 0.6) to that reported by Briseño-Dueñas (1998) for El Verde Camacho (Campista-León et al, 2019); therefore, the importance of monitoring and conserving SPC and the need for more studies at PC are highlighted due to the increasing numbers of nests. In addition, climatic variations, such as the El Niño Southern Oscillation (ENSO), can influence the reproductive success of sea turtles (Santidrián Tomillo et al, 2020); these climatic variations could have no effect or a moderate effect on olive ridley turtle nesting (Ariano-Sánchez et al, 2020;Santidrián Tomillo et al, 2020).…”
Section: Discussionsupporting
confidence: 76%